2017
DOI: 10.4038/engineer.v50i2.7251
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Rainfall in Sri Lanka during 1966 – 2015

Abstract: Abstract:The aim of this study was to analyse the annual and seasonal rainfall trends in Sri Lanka during the 50 year period from 1966 to 2015 using rainfall data collected at 32 rain gauging stations. The seasons considered were the two principal monsoon seasons and the two inter-monsoon seasons. Non-parametric Mann-Kendall trend test and Sen's Slope estimator method were used to examine the rainfall trends and determine their magnitudes. According to the analysis which was based on annual rainfall data, 21 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 6 publications
7
32
0
Order By: Relevance
“…Similar to the above findings, Karunathilaka et al, (2017) in their study revealed that the eastern region of the country has shown an increasing trend in rainfall over the last half century, while western, northern and south-western region and central hill of the country have shown a decreasing rainfall trend during the same period. As like the annual total rainfall monthly and seasonal rainfall also show an important pattern in this district.…”
Section: Fig 1: Annual Total Rainfall From 1918 -2017supporting
confidence: 82%
See 1 more Smart Citation
“…Similar to the above findings, Karunathilaka et al, (2017) in their study revealed that the eastern region of the country has shown an increasing trend in rainfall over the last half century, while western, northern and south-western region and central hill of the country have shown a decreasing rainfall trend during the same period. As like the annual total rainfall monthly and seasonal rainfall also show an important pattern in this district.…”
Section: Fig 1: Annual Total Rainfall From 1918 -2017supporting
confidence: 82%
“…These two prime monsoons (South-West and North-East Monsoons) are responsible for distinct cropping seasons known as Yala and Maha. Karunathilaka et al, (2017) emphasizes that, the seasonal rainfall indicates an increasing trend during the first-inter monsoon, second-inter monsoon and north-east monsoon seasons at a majority of the stations.…”
Section: Introductionmentioning
confidence: 78%
“…Ratnapura district is in wet zone of the country. This area is highly vulnerable to frequent flooding due to higher rainfall volumes (Eriyagama et al 2010;Karunathilaka et al 2017). Rathnapura district receives a significant rainfall from SW monsoon from May to September (Punyawardena and Cherry 1999).…”
Section: Case Study Application-erathna Mini-hydropower Plantmentioning
confidence: 99%
“…However, they found that the intensity of rainfall was increasing. In addition, Ranatunge et al (2003), Jayawardene et al (2005), Wickramagamage (2016) and Karunathilaka et al (2017) have put efforts in studying annual and seasonal rainfall trends in Sri Lanka. (Khaniya et al 2018) presented some interesting rainfall trend analyses and linked them with the hydropower generation of a ROR hydropower plant.…”
Section: Introductionmentioning
confidence: 99%
“…However, around two-day continues 75 -100 mm rainfall can trigger landslides in sloped cultivated lands in Badulla [22]. In Sri Lanka, an increasing trend in high intense rainfall event during last decade is recorded, especially in the Wet Zone and western slopes in the central hills [23]. Also, the frequency of landslide events per year has increased over the last few decades.…”
Section: Introductionmentioning
confidence: 99%